The Effects of Teaching Communication Skills to Nursing Students on the Quality of Care for Patients - Motaarefi, Hossein (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Nursing profession requires not only the academic knowledge but also the interpersonal relationships, technical, and intellectual abilities. Aim: This study aimed to determine the impact of teaching communication skills to nurse students on the quality of care given by nursing students. Materials and Methods: This study was a quasi-experimental research that was performed on 66 past year students and 132 patients using a goal-oriented sampling method in 2016. The data collection tools included a demographic information form of the units under study, a checklist of studentsâ€™ communication skills, and a quality of care questionnaire for patients (QualPaC). The study tools were completed by the students and patients before the intervention and after completion of the training course. After collection, data were analyzed using SPSS v16 and descriptive and inferential statistics such as paired t-test and Pearson correlation coefficient. Results: The results showed that there was a significant difference between the mean quality of patientsâ€™ care before and following the intervention (P â‰¤ 0.001). Furthermore, there was a significant difference between the means for nursing studentâ€™s communication skills before and after the intervention. Moreover, there was a significant correlation between the mean scores of students and the quality of care and communication skills (P â‰¤ 0.001). Conclusion: It is recommended that the professionals in the field of nursing incorporate â€œcommunication skillsâ€ into their instructional programs so that the nursing students acquire the requisite experience in the field before entering into this profession. Furthermore, teaching communication skills should be followed up after the studentsâ€™ graduation.